Penerapan Metode Konstruktivisme untuk Meningkatkan Kemampuan Menulis Narasi Siswa Kelas VII SMPN Satap Heut’utan - Idalia Cardoso (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2018)
Writing is one of language comprehensions used to indirect communication to other people. Narration writing skill is one of language comprehension aspects taught in Indonesian language teaching. Narration writing skill of students at first grade of SMPN Satap Heut Utan is still in low category. Furthermore, it is necessary to find solution to increase writing skill. This research aims at increasing narration writing skill using constructivism theory to those students in academic year 2017/2018. Method used in this research class action research to describe students’ comprehension in writing narrative text by noticing mark, spelling, diction, sentence arrangement and paragraph developing. Based on analysis, it can be concluded that, narration writing skill of those students is increasing. It can be shown by narration writing score by using five aspects with score 1 % for mark, 2 % for spelling, 3 % for diction and vocabulary, 4 % for sentence arrangement and 5 % for paragraph developing.